Women's Stories and Boasian Texts: The Ojibwa Ethnography of Ruth Landes and Maggie Wilson - Cole, Sally (Anthropologica, 2022)
The conventional interpretation of Ruth Landes's 1930s writings on Ojibwa culture is that Landes described the society as individualistic, "atomistic" and conflict-ridden. Contemporary and subsequent ethnographers disputed this interpretation and instead emphasized co-operative and egalitarian social relations. This article argues that conflict in Landes's ethnography be read less as a representation of Ojibwa culture itself than as a product of tensions between three storytelling practices: the Boasian textual tradition; Ojibwa women's storytelling; and the cultural script for American daughters of Russian Jewish immigrants (like Landes). The article describes how these storytelling practices mediated the collaboration between anthropologist Ruth Landes and her key informant Maggie Wilson. It further argues that the key to under standing the collaboration is not their gender but rather the marginalization that both women experienced as individuals within their own cultural contexts. Widely differing though these contexts were, it was their shared understanding of outsider status that enabled Ruth Landes and Maggie Wilson to explore the terrain of conflict and contradiction in the lived experience of culture.